2005
DOI: 10.1002/icd.420
|View full text |Cite
|
Sign up to set email alerts
|

Whining as mother-directed speech

Abstract: Although little studied, whining is a vocal pattern that is both familiar and irritating to parents of preschool‐ and early school‐age children. The current study employed multidimensional scaling to identify the crucial acoustic characteristics of whining speech by analysing participants' perceptions of its similarity to other types of speech (question, neutral speech, angry statement, demand, and boasting). We discovered not only that participants find whining speech more annoying than other forms of speech,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…In this connection, we would submit that whining could serve as a transitional form of crying, as the child becomes more physically independent and linguistically competent. Whining is a vocalization, often coupled with speech, which is used to make a request (e.g., for food), lodge a complaint, or represent discontent (Sokol, Webster, Thompson, & Stevens, 2005). It has been suggested that whining shares with crying the specialized acoustic characteristics of increased pitch and varied pitch patterns.…”
Section: Specific Priorities For Further Explorationmentioning
confidence: 99%
“…In this connection, we would submit that whining could serve as a transitional form of crying, as the child becomes more physically independent and linguistically competent. Whining is a vocalization, often coupled with speech, which is used to make a request (e.g., for food), lodge a complaint, or represent discontent (Sokol, Webster, Thompson, & Stevens, 2005). It has been suggested that whining shares with crying the specialized acoustic characteristics of increased pitch and varied pitch patterns.…”
Section: Specific Priorities For Further Explorationmentioning
confidence: 99%
“…For this method, using Praat 4.2.14 (Boersma & Weenink, 2004), each segment was analyzed to evaluate its pitch, rate of production (e.g. length of spoken portions and inhalations), and variation in pitch, all of which are salient characteristics of whining and motherese (see Sokol et al, 2005 for full details). This approach revealed that the whining and motherese stimuli exhibited these characteristics in comparison to the neutral speech sufficient for use in this experiment (see Table 1).…”
Section: Stimulimentioning
confidence: 99%
“…Whines enter into a child's vocal repertoire with the onset of language, typically peaking between 2.5 and 4 years of age (Borba, 2003; Sears & Sears, 1995). This sound is perceived as more annoying even than infant cries (Sokol et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Whining is generally considered unpleasant and unwanted (Edwards, 2005). Defined as "a low somewhat shrill protracted cry" (Oxford English Dictionary), the distinctive intonational pattern of whining involves exaggerated rising pitch contours, increased loudness, and slower production (Sokol, et al, 2005). While this makes whining a useful attention-getting practice, whining has been found to be more annoying and distracting than other speech forms (Chang & Thompson, 2010).…”
Section: Introductionmentioning
confidence: 99%